The Effect of Dietary Fat and Sucrose on Cognitive Functioning in Mice Lacking Insulin Signaling in Neuropeptide Y Neurons - Mitchell, Caitlin S.; Goodman, Elisabeth K.; Tedesco, Caitlin R.; Nguyen, Kathy; Zhang, Lei; Herzog, Herbert; Begg, Denovan P. (Frontiers in Physiology, 2022)
Obesogenic diets can produce hippocampal insulin resistance and impairments to hippocampal-dependent cognition. This study investigated the effect of disrupted insulin signaling in Neuropeptide Y (NPY) neurons on diet-induced deficits in hippocampal-dependent memory. Wild-type mice and mice that had a targeted knockout of insulin receptors on NPY cells (IRlox/lox;NPYCre/+) were given ad libitum access to a high-fat diet (high fat; HF), 10% sucrose solution (high sugar; HS), both high-fat diet and sucrose solution (high fat, high sugar; HFHS), or a normal fat control chow for 12 weeks. Mice were tested in the Morris Water Maze (MWM), a hippocampal-dependent spatial memory task. Glucose homeostasis was assessed via a glucose tolerance test. Independent of genotype, consumption of HF, but not HS, diet increased energy intake, body weight, and plasma leptin, and impaired glucose tolerance. Disrupted insulin signaling in NPY cells and dietary interventions did not significantly affect the ability of mice to learn the location of the platform in the MWM. However, for IRlox/lox control mice, consumption of HF, but not HS, diet resulted in reduced time spent in the target quadrant during the probe trial, suggesting a hippocampal-dependent memory deficit. IRlox/lox;NPYCre/+ mice had poor performance in the probe trial regardless of diet, suggesting a floor effect. This study did not find adverse effects of chronic sucrose intake on metabolic outcomes or hippocampal-dependent memory. These data also suggest that the effects of HF diet on hippocampal-dependent memory may be dependent on insulin signaling in hippocampal NPY cells.